1998
DOI: 10.1016/s0006-3495(98)78001-4
|View full text |Cite
|
Sign up to set email alerts
|

Slow Inactivation in Human Cardiac Sodium Channels

Abstract: The available pool of sodium channels, and thus cell excitability, is regulated by both fast and slow inactivation. In cardiac tissue, the requirement for sustained firing of long-duration action potentials suggests that slow inactivation in cardiac sodium channels may differ from slow inactivation in skeletal muscle sodium channels. To test this hypothesis, we used the macropatch technique to characterize slow inactivation in human cardiac sodium channels heterologously expressed in Xenopus oocytes. Slow inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
110
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 27 publications
8
110
1
Order By: Relevance
“…Namely, these authors reported channel activation (36,45), as well as fast and slow inactivation (24,45), to occur at more hyperpolarized potentials in Na v 1.5 compared with Na v 1.4 channels. In addition, Na v 1.5 channels exhibited slowed kinetics of fast inactivation (24, 45), a reduced voltage dependence of slow inactivation (24), and a higher resistance to undergo slow inactivation (24,31). All these Na v 1.4-toNa v 1.5 shifts in Na ϩ current parameters were also found in our cardiac-conditioned compared with control cells (compare values in Tables 1 and 2).…”
Section: Differentiation Of Control and Cardiac-conditioned Cellsmentioning
confidence: 74%
See 3 more Smart Citations
“…Namely, these authors reported channel activation (36,45), as well as fast and slow inactivation (24,45), to occur at more hyperpolarized potentials in Na v 1.5 compared with Na v 1.4 channels. In addition, Na v 1.5 channels exhibited slowed kinetics of fast inactivation (24, 45), a reduced voltage dependence of slow inactivation (24), and a higher resistance to undergo slow inactivation (24,31). All these Na v 1.4-toNa v 1.5 shifts in Na ϩ current parameters were also found in our cardiac-conditioned compared with control cells (compare values in Tables 1 and 2).…”
Section: Differentiation Of Control and Cardiac-conditioned Cellsmentioning
confidence: 74%
“…To substantially improve cardiac contractility, the skeletal muscle graft should contract in synchrony with host cardiac tissue. This requires both electrical coupling between skeletal muscle cells and cardiomyocytes and cardiac ion channel function in skeletal muscle cells (31,35). Electrical coupling does occur in vitro (10,14,28) but has seriously been questioned in vivo (16,17,34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When channels undergo the structural change resulting in inactivation, no amount of electrical stimulus can open the channel, and this is known as the refractory period. Slow inactivation can occur over several seconds and may serve to regulate the excitability of the cell when it is undergoing repetitive depolarizations [27]. Fast inactivation is believed to occur through a Bhinged lid^mechanism from the loop located in between domains III and IVon the inside of the cell.…”
Section: Cardiac Sodium Channels Normal Physiologymentioning
confidence: 99%